2020
DOI: 10.25273/jpfk.v6i1.5579
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Instrumen Tes Pemecahan Masalah Bagi Mahasiswa Jurusan Fisika Pada Materi Dinamika Partikel

Abstract: Kemampuan pemecahan masalah merupakan salah satu kemampuan yang penting dimiliki oleh semua orang khususnya para mahasiswa yang sedang menempuh studi di jurusan fisika. Hal ini dikarenakan fisika merupakan ilmu yang sangat erat kaitannya dengan kehidupan sehari-hari. Sebagai mahasiswa, diperlukan adanya instrument tes yang dapat mengukur kemampuan pemecahan masalah yang dimiliki agar dapat diukur apakah kemampuan dalam proses pemecahan masalah yang dimiliki telah mencukup atau belum mencapai minimum. Telah ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The results of the three field tests showed that there was an increase in the quality of the question items after being revised 3 times, so that of the 15 test items developed, there were 14 test items that were suitable for inclusion in the question bank and used as problem-solving based test instruments for SMA/MA level. The research is in line with (Kurniawan & Taqwa, 2018) which shows that 7 test items representing four indicators of dynamic electrical material have good validity and reliability.…”
Section: Discussionsupporting
confidence: 78%
“…The results of the three field tests showed that there was an increase in the quality of the question items after being revised 3 times, so that of the 15 test items developed, there were 14 test items that were suitable for inclusion in the question bank and used as problem-solving based test instruments for SMA/MA level. The research is in line with (Kurniawan & Taqwa, 2018) which shows that 7 test items representing four indicators of dynamic electrical material have good validity and reliability.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, the teacher can also assess student activities while the learning process is ongoing (Khaerunnisa & Pamungkas, 2018;Srirahayu & Arty, 2018). Instruments can facilitate collecting student learning outcomes (Darmawan et al, 2020;Hamidah & Wulandari, 2021). Assessment can also be interpreted as an effort to interpret the measurement results into meaningful information for students (Khaerunnnisa & Pamungkas, 2018;Lestari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Keterampilan pemecahan masalah perlu dimiliki oleh peserta didik (Kurniawan et al, 2018). Guru sebagai fasilitator pembelajaran perlu mengembangkan dan menggunakan insrumen evaluasi yang dapat memberikan kesempatan kepada peserta didik mengembangkan keterampilan pemecahan masalahnya.…”
Section: Pendahuluanunclassified